KONSTRUKSI KESIAPAN MENTAL ORANG TUA DALAM PERSPEKTIF TAFSIR AL-MISHBAH: ANALISIS INTEGRATIF QS. LUQMAN 13–19 DAN QS. AN-NISA’ 9 - Muhammad Irhamsyah; Agusman Damanik (IAIN KENDARI, 2026)
This study examines parental mental readiness from a Qur’anic perspective through an integrative analysis of Surah Luqman (13–19) and Surah An-Nisa’ (9) based on Tafsir Al-Mishbah. The research is motivated by the dominant emphasis on financial readiness in family formation, which often neglects the mental and spiritual preparedness of parents. This study employs a qualitative approach using library research and thematic exegesis analysis. The findings reveal that parental mental readiness is a multidimensional construct consisting of five main dimensions: monotheism, reciprocity, emotional regulation, social morality, and responsibility. The model aligns with modern parenting theories, such as emotional intelligence and authoritative parenting, yet offers a distinctive contribution through the integration of spiritual dimensions as its foundation. Theoretically, this study contributes to the development of constructive thematic exegesis, while practically providing a conceptual basis for Islamic family education. Future studies are recommended to empirically test this model